Kappa opioid receptor/dynorphin system: Genetic and pharmacotherapeutic implications for addiction - Butelman, Eduardo R. (2012)
Addictions to cocaine or heroin/prescription opioids [short-acting mu-opioid receptor (MOPr) agonists] involve relapsing cycles, with experimentation/escalating use, withdrawal/abstinence, and relapse/re-escalation. Kappa-opioid receptors (KOPr; encoded by OPRK1), and their endogenous agonists, the dynorphins (encoded by PDYN) have counter-modulatory effects on reward caused by cocaine or MOPr agonist exposure, and exhibit plasticity in addictive-like states. KOPr/dynorphin activation is implicated in depression/anxiety, often co-morbid with addictions. In this Opinion article, we propose that particular stages of the addiction cycle are differentially affected by KOPr/dynorphin systems. Vulnerability and resilience can be due to pre-existing (e.g., genetic) factors, or epigenetic modifications of the OPRK1 or PDYN genes during the addiction cycle. Pharmacotherapeutic approaches limiting changes in KOPr/dynorphin tone, especially with KOPr partial agonists, may hold potential for the treatment of specific drug addictions and psychiatric co-morbidity.